1999
DOI: 10.1007/3-540-48714-x_10
|View full text |Cite
|
Sign up to set email alerts
|

Co-dimension 2 Geodesic Active Contours for MRA Segmentation

Abstract: Automatic and semi-automatic magnetic resonance angiography (MRA) segmentation techniques can potentially save radiologists large amounts of time required for manual segmentation and can facilitate further data analysis. The proposed MRA segmentation method uses a mathematical modeling technique which is well-suited to the complicated curve-like structure of blood vessels. We define the segmentation task as an energy minimization over all 3D curves and use a level set method to search for a solution. Our appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 13 publications
0
59
0
1
Order By: Relevance
“…For instance, Whitaker [23] proposes a nonlinear reweighting scheme that favors the smaller curvature and preserves cylindrical structures. Lorigo et al [24] propose a smoothing by the minimum curvature.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, Whitaker [23] proposes a nonlinear reweighting scheme that favors the smaller curvature and preserves cylindrical structures. Lorigo et al [24] propose a smoothing by the minimum curvature.…”
Section: Related Workmentioning
confidence: 99%
“…Comparison is based on the orientation discrepancy (function δ in Equation 7) between the estimated and the truth flow iso-surface normals 4 . In OT, a 5 × 5 × 5 filter window with relative bandwidth B equals 2 and center frequency ρ equals π 2 √ 2 has been used; a 3 × 3 Gaussian kernel with σ = 1 has been employed for tensor averaging (for further details, see Chapter 6 in [22]).…”
Section: Validation Of Local Orientation Estimationmentioning
confidence: 99%
“…For instance, authors in [2], [3] demonstrated that the expectation maximization (EM) algorithm and a maximum likelihood (ML) estimate can be used to segment vascular structures automatically with a proper statistical mixture model. The use of gradient information to drive evolving contours with the level set method and topologically adaptable surfaces to segment vasculature in the angiograms has been proposed in [4], [5], [6], [7]. Region-growing approaches to segmenting the angiograms with initial segmentations have been illustrated in [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…To smooth the tracts while segmenting them we regularize the flow by adding a curvature dependent speed. Lorigo et al introduced the use of a curvature definition from codimension 2 flows on surfaces with a thin, tubular structure [21]. Instead of using either mean curvature or gaussian curvature, which will normally destroy the tubular structure, they use the smaller principal curvature which is a combination of both curvatures.…”
Section: Regularizationmentioning
confidence: 99%